Supplementing Brachiaria Hybrid and Pennisetum Purpureum with Pueraria Phaseoloides increased the Concentration of rumen undegradable protein in forage-based diets for ruminants. - Hughes, Martin; Leon, Elisha; Daley, Oral (My University, 2023)
See attached.
Dataset included.
Keywords: Ruminants—Feeding and feeds -- Trinidad and Tobago; Animals—Food